Effects of shoulder manipulation on electromyography measures in archery athletes during recovery from fatigue: a comparison between sexes - Rafał Studnicki; Weronika Naderza; Bartłomiej Niespodziński; Rita Hansdorfer-Korzon; Adam Kawczyński (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The aim of this study was to analyze the effects of manual therapy on electromyography (EMG) measures of the primary muscles involved in archery, considering the differences between sexes. Twenty trained archery athletes (men: 14, age: 32.1±6.6 years; women: 6, age: 25.3±5.0 years) participated in this experimental study. The athletes were subjected to 100 archery shots, after which they received regenerative manual therapy. EMG measurements were taken from the middle deltoid, posterior deltoid, upper trapezius, middle trapezius, lower trapezius, and infraspinatus muscles before the shots, after the shots, and after the manual therapy. The outcomes measured included the mean and maximal amplitude of the EMG root mean square (EMGRMS) and the median frequency of the raw surface EMG signal power spectrum (EMGMED). Sex comparisons revealed a significantly higher EMGMED in the upper trapezius following manual therapy in women compared to men (F=5.096; p=0.037). No other significant differences were found between sexes (p>0.05). Repeated measures conducted at baseline, after 100 shots, and after manual therapy showed a significantly greater mean amplitude EMGRMS in the infraspinatus following manual therapy compared to after 100 shots (169.7 vs. 109.8 µV; p=0.008). Similar results were noted for maximal amplitude EMGRMS (372.7 vs. 209.5 µV; p=0.010). Additionally, a significantly lower maximal amplitude EMGRMS was observed at baseline compared to after manual therapy in low trapezius (312.6 vs. 551.2 µV; p=0.045). In summary, and overall, manual therapy did not play a significant role in restoring the EMG parameters in the primary muscles of archers after exposure to a fatigue condition. However, it showed efficacy in the case of the infraspinatus. Furthermore, apart from the upper trapezius, no significant effects were observed between genders, indicating similar effects in both.